Classification of Tools For Feature-Oriented Software Development: A Comprehensive Review - Kala, KU; Nandhini, M (International Journal of Computer Sciences and Engineering, 2025)
Software development tools are the programs or set of programs which assist the software developers in the development of other programs and applications. This makes their work easier. Feature-Oriented Software Development (FOSD) Paradigm is a software development paradigm especially for the development of large-scale software systems and software product lines. Like every other software development paradigm, the complexity of the creation, debugging and maintenance of a Feature-Oriented software development necessitate the tool support. Software product-line development consists of multiple phases (Domain Analysis, Domain Design and Specification, Domain Implementation, and Product Configuration and Generation), each of which shall be supported by proper tools. There are a large number of tools available for supporting each process of FOSD, but proper classification does not exist. Tools which support one phase will not support the processes of other phases, so it is necessary to study the tools available before using it. In this review, our aim is to collect and classify the available tools based on the processes of each phase of FOSD. As the supporting tool field is too broad and continuously changing, the collective information about tools is not available. This review helps the developers and researchers to get a comprehensive idea of the existing tools and their functions, which help them to make use of this according to their need.